Research into cavitation processes in the trapped volume of the gear pump - Kostiuk, Dmytro; Kolesnikov, Denis; Stas, Serhiy; Yakhno, Oleh (Eastern-European Journal of Enterprise Technologies, 2018)
We investigated processes in the trapped volume of the gear pump, formed due to the peculiarities in the geometry of the involute gearing characteristic of the pumps of a given type. In the fluid confined to a trapped volume, at gear rotation, there occur a series of complex hydrodynamic processes. A change in the magnitude of the trapped volume leads to the occurrence of fluid compression, as well as its rarefaction. Reducing the pressure in a fluid below the level of a saturated vapour pressure results in the emergence of cavitation in it. In addition, the result of gear rotation is the vortex motion of fluid that leads to eddies, in the centre of which there is a reduction in pressure; in other words, vortices are the potential embryos of cavitation. High-speed video registration makes it possible to consider in detail the process of emergence and growth of cavitation phenomena in a trapped volume, to explore the dynamics of deformation of a cavitation bubble and a cavity, formed in the trapped volume. Based on the results of processing the sequences of frames acquired in the course of this study, we derived dependences that show the character of change in the size of a cavitation bubble and a cavity. The constructed dependences are non-linear and have points of an extremum. The extremum in the time-dependent chart is observed after opening the trapped volume, meaning that it would take some time (approximately 1 ms) for the pressure in a intertooth cavity to grow. In this case, the extremum is observed almost simultaneously both for the deformation of the cavity and the deformation of a single bubble. The radius of a bubble in a liquid depends on individual factors, namely, properties of the fluid and the pressure magnitude, which can be calculated by applying the dependences, given in this work, depending on the conditions for the occurrence of cavitation.